2003
DOI: 10.1073/pnas.0932778100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the β cell antigen targeted by a prevalent population of pathogenic CD8+T cells in autoimmune diabetes

Abstract: Type 1 diabetes is an autoimmune disease in which autoreactive T cells attack and destroy the insulin-producing pancreatic ␤ cells. CD8 ؉ T cells are essential for this ␤ cell destruction, yet their specific antigenic targets are largely unknown. Here, we reveal that the autoantigen targeted by a prevalent population of pathogenic CD8 ؉ T cells in nonobese diabetic mice is islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP). Through tetramer technology, IGRP-reactive T cells are readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
373
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(383 citation statements)
references
References 31 publications
8
373
1
1
Order By: Relevance
“…8.3 NOD CD8 + T cells recognise an immuno-dominant peptide from IGRP, termed IGRP 206-214 , a protein expressed by pancreatic beta cells, and these cells are representative of a significant fraction of CD8 + T cells in pancreatic islets at the onset of inflammation [23,28,29]. Adoptive transfer of IGRP-specific (islet antigen) CD8 + T cells [26] into infected NOD mice confirmed an increase in the proliferation and activation of these cells in the pancreatic LNs (Fig.…”
Section: Wt C Rodentium Infection Disrupts Intestinal Barrier Functimentioning
confidence: 99%
“…8.3 NOD CD8 + T cells recognise an immuno-dominant peptide from IGRP, termed IGRP 206-214 , a protein expressed by pancreatic beta cells, and these cells are representative of a significant fraction of CD8 + T cells in pancreatic islets at the onset of inflammation [23,28,29]. Adoptive transfer of IGRP-specific (islet antigen) CD8 + T cells [26] into infected NOD mice confirmed an increase in the proliferation and activation of these cells in the pancreatic LNs (Fig.…”
Section: Wt C Rodentium Infection Disrupts Intestinal Barrier Functimentioning
confidence: 99%
“…In NOD mice, several peptides from these autoantigens have been identified as targets of T cell responses. These include GAD65 p524-543 and p246-266 [1, 2], GAD65 p206-220 and p286-300 [3], insulin B chain p9-23 [4,5], proinsulin p24-33 (proinsulin II p48-57) [6],, and insulin-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) p206-214 [8]. Extensive analysis of TCR BV gene usage and CDR3 sequences have demonstrated that the early islet-infiltrating T cell clonal expansion is restricted to distinct BV families, e.g., BV4 [9], BV2, BV12, BV14 [10], BV13 [11], BV8.2 [12], and BV1 [13].…”
mentioning
confidence: 99%
“…For some of these novel autoantigens, there is data suggesting their significant role in the development of T1D, such as the existence of T-cell clones capable of transferring the disease or immunotherapy using antigenic peptides derived from these autoantigens (Table 1). These include islet-specific glusose-6-phosphatase catalytic subunitrelated protein (IGRP), ZnT8 and, interestingly, the neurotropic factor S100beta and the glial fibrillary acidic protein (GFAP) (Gomez-Tourino et al 2010Lieberman et al 2003;Trudeau et al 2003;Winer et al 2003), the latter two being antigens not expressed by the beta cells themselves but by a group of nerve cells surrounding the islets called the peri-islet Schwann cells (pSC) which makes their role in T1D pathogenesis controversial.…”
Section: T Lymphocytes In T1d: Targets and Peripheral Detectionmentioning
confidence: 99%
“…IGRP antigen was first identified as the antigen targeted by a prevalent population of pathogenic CD8 + T cells in NOD mice (Lieberman et al 2003) and also by human T lymphocytes . Its relevance to T1D derives from the fact that in the NOD mice the number of IGRP-specific CD8 + T cells correlate with the future development of clinical disease (Trudeau et al 2003).…”
Section: T Lymphocytes In T1d: Targets and Peripheral Detectionmentioning
confidence: 99%